Penilaian Standar Mutu Pada Aplikasi Parkir Universitas Muhammadiyah Gresik Dengan ISO 9241-11 Dan Fishbone Analisis - Muhammad Iqbal Waliyuddiin; Yudha Arya Prasaja; Farid Sukmana; Adryan Firdaus (Puslitbang Sekawan Institute Nusa Tenggara, 2021)
The parking application service at the University of Muhammadiyah Gresik is an update from the previous system. Of course, this application requires a system that is practical, efficient, and also has good data storage security. One of the references that can be used that these things have been fulfilled in this application is an analysis using ISO 9241-11. The purpose of this study was to analyze the application of UMG parking for the feasibility of ISO 9241-11. Analytical research methods used include determining clauses, checklists, Likert scales, maturity levels, and fishbone diagrams. Clause, checklist use for getting assessment based on the park system, then from that result will be used to get the qualification of this system with liket scale in each clause of this standard, and assessment of all clause with likert scale , the result of level quality assurance of this system will be found. Next the using fishbone diagram can analyze to get the root cause of clause dan quality assurance in ISO 9241-11. Because that , with this study we can know the qualification and the root cause of park system. And the analysis using that tool, this system still not suitable to use ISO 9241-11. The parent of root cause is in efficiency clause in organitation like less costing and planning.